Results of Measuring Lactate Levels Value in Free Flap Reconstruction - Muzakkie, Mufida; Adhania, Karnissa Rizkia (Lingkar Studi Bedah Plastik Foundation, 2024)
Introduction : Free flap surgery which is performed by transferring tissue along with its vascularization, can fail due to vascular compromised which cause by thrombosis formation either in vein or artery. Disruption of blood flow patency that not treated immediately can cause ischemia and necrosis occurred in free flap, especially within five days after reconstruction. Previous study has proven that free flap monitoring with lactate levels measurement can accurately for evaluate the occurrence vascular compromised in free flap. Method : This study is a descriptive observational study with cross-sectional design. It was conducted by observing medical record of free flap reconstruction patient from November 2022 until November 2023 at Plastic and Reconstructive Surgery Department of RSUP Dr. Mohammad Hoesin Palembang. Data collection was carried out using total sampling technique and analysed using Statistical Package for the Social Science (SPSS) version 22.0 with univariate technique. Result : Free flap with vascular compromise has higher lactate levels value than viable one. Lactate levels value transition of viable free flap showed an increase after anastomosis and gradually decrease at the next assessment time, while lactate levels in free flap with vascular compromise increased to above reference value, mainly on the first day vascular compromise occurred. Conclusion: Clinical monitoring which combined with lactate levels assessment can accelerate the diagnose of blood flow patency disruption in free flap so that cause success rate improvement and better prognosis of free flap reconstruction patients.